Molecular structure, infrared spectra, photochemistry, and thermal properties of 1-methylhydantoin - Nogueira, Bernardo A. (2014)
The structural, vibrational, and photochemical study of 1-methylhydantoin (1-MH, C4H6N2O2) was undertaken by matrix isolation infrared spectroscopy (in argon matrix; 10 K), complemented by quantum chemical calculations performed at the DFT(B3LYP)/6-311++G(d,p) level of approximation. The theoretical calculations yielded the Cs symmetry structure, with planar heavy atom skeleton, as the minimum energy structure on the potential energy surface of the molecule. The electronic structure of this minimum energy structure of 1-MH was then studied in detail by means of the natural bond orbital (NBO) and atoms in molecules (AIM) approaches, allowing for the elucidation of specific characteristics of the molecule's σ and π electronic systems. The infrared spectrum of the matrix-isolated 1-MH was fully assigned, also with the help of the theoretically predicted spectrum of the compound, and its UV-induced unimolecular photochemistry (λ ≥ 230 nm) was investigated. The compound was found to fragment to CO, isocyanic acid, methylenimine, and N-methyl-methylenimine. Finally, a thermal behavior investigation on 1-MH samples was carried out using infrared spectroscopy (10 K until melting), differential scanning calorimetry and polarized light thermal microscopy. A new polymorph of 1-MH was identified. The IR spectra of the different observed phases were recorded and interpreted.